Історичні ойконіми українсько-польського пограниччя: семантично-словотвірні паралелі - Редьква, Ярослав Петрович; Редьква, Ярослав Петрович (My University, 2024)
Historical spatial oikonyms of western Ukrainian and eastern Polish borderland with helonym hydrographical terms *lug (*lǫgъ / *lęgъ), luża (< *lougja), :*lǫkъ, *lǫka , *lǫkja, *lǫkavъ,*lǫkavьсь in the stems were analysed in our study. In present-day Lviv, Ternopil and Ivano-Frankivsk Oblasts in the western Ukraine and Lublin and Podkarpackie Voivodeships in eastern Poland etymologies of thirty-three place names were established: Zaluzhzhia, Zalukva, Zaluchchia, Pidluzhzhia, Naluzhzhia, Zaluzhany (Zaluzhzhia), Pidluzhzhia, Dołhołęka, Głęboka Łąka, Łęg, Łąkowe, Łąki Henrykowskie, Łużek, Łączki, Nad Łąkami, Podłąka, Załuże etc.
Keywords: oikonyms, Ukrainian-Polish borderland, semantic-derivational parallel, historical oikonymy